(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The Prelude or, Growth of a Poet’s Mind; AnAutobiographical Poem is an autobiographical conversationpoem[1] in blank verse bythe English poet William Wordsworth. Intended as the introductionto the more philosophical Recluse, which Wordsworth neverfinished, The Prelude is an extremely personal and revealingwork on the details of Wordsworth’s life. Wordsworth began The Prelude in1798 at the age of 28 and continued to work on it throughout his life. He nevergave it a title; he called it the "Poem (title not yet fixed upon)to Coleridge" and in his letters to Dorothy Wordsworth referred to it as"the poem on the growth of my own mind". The poem was unknown to thegeneral public until published three months after Wordsworth’s death in 1850,its final name given to it by his widow Mary.